Electronic Population Transfer via Impulsive Stimulated X-Ray Raman Scattering with Attosecond Soft-X-Ray Pulses - O’Neal, Jordan T.; Champenois, Elio G.; Oberli, Solène; Obaid, Razib; Al-Haddad, Andre; Barnard, Jonathan; Berrah, Nora; Coffee, Ryan; Duris, Joseph; Galinis, Gediminas; Garratt, Douglas; Glownia, James M.; et al. (My University, 2020)
Free-electron lasers provide a source of x-ray pulses short enough and intense enough to drive nonlinearities in molecular systems. Impulsive interactions driven by these x-ray pulses provide a way to create and probe valence electron motions with high temporal and spatial resolution. Observing these electronic motions is crucial to understand the role of electronic coherence in chemical processes. A simple nonlinear technique for probing electronic motion, impulsive stimulated x-ray Raman scattering (ISXRS), involves a single impulsive interaction to produce a coherent superposition of electronic states. We demonstrate electronic population transfer via ISXRS using broad bandwidth (5.5 eV full width at half maximum) attosecond x-ray pulses produced by the Linac Coherent Light Source. The impulsive excitation is resonantly enhanced by the oxygen 1s→2π∗ resonance of nitric oxide (NO), and excited state neutral molecules are probed with a time-delayed UV laser pulse.